2009
DOI: 10.1007/s00125-009-1493-6
|View full text |Cite
|
Sign up to set email alerts
|

Podocytes produce homeostatic chemokine stromal cell-derived factor-1/CXCL12, which contributes to glomerulosclerosis, podocyte loss and albuminuria in a mouse model of type 2 diabetes

Abstract: Aims/hypothesis Chemokine (C-X-C motif) ligand 12 (CXCL12) (also known as stromal cell-derived factor-1 [SDF-1]-alpha) is a homeostatic chemokine with multiple roles in cell homing, tumour metastasis, angiogenesis and tissue regeneration after acute injuries. However, its role in chronic diseases remains poorly defined, e.g. in chronic glomerular diseases like diabetic glomerulosclerosis. We hypothesised that CXCL12 may have a functional role during the evolution of diabetic glomerulosclerosis, either by assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
110
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 53 publications
11
110
0
Order By: Relevance
“…In patients with type 1 diabetes, we have focused on the effect of acute hyperglycaemia on the urinary excretion of cytokines/chemokines rather than tissue expression of these factors, hypothesising that urinary excretion of inflammatory mediators correlates with tissue expression. Similar to observations made in animal studies, we demonstrated that acute hyperglycaemia influences urinary cytokine/chemokine excretion, suggesting that the link between intraglomerular pressure, inflammation and renal injury also exists in humans [1][2][3]6]. From a more clinical perspective, we have demonstrated that increased urinary cytokine/chemokine excretion precedes the onset of early clinical manifestations of nephropathy, including microalbuminuria, in young patients with type 1 diabetes [7].…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…In patients with type 1 diabetes, we have focused on the effect of acute hyperglycaemia on the urinary excretion of cytokines/chemokines rather than tissue expression of these factors, hypothesising that urinary excretion of inflammatory mediators correlates with tissue expression. Similar to observations made in animal studies, we demonstrated that acute hyperglycaemia influences urinary cytokine/chemokine excretion, suggesting that the link between intraglomerular pressure, inflammation and renal injury also exists in humans [1][2][3]6]. From a more clinical perspective, we have demonstrated that increased urinary cytokine/chemokine excretion precedes the onset of early clinical manifestations of nephropathy, including microalbuminuria, in young patients with type 1 diabetes [7].…”
Section: Introductionsupporting
confidence: 86%
“…Experimental data have suggested the association of high intraglomerular pressure with increased shear stress in diabetes, leading to renal injury [1][2][3]. The pathogenesis of hyperfiltration remains controversial; both haemodynamic (the 'haemodynamic hypothesis') and tubuloglomerular feedback mechanisms (the 'tubular hypothesis') have been implicated [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spiegelmer antagonists to a number of extracellular targets have been described (11,14,24,35). Two Spiegelmers have proven to be safe and well tolerated in Phase I clinical studies 4 providing evidence that the Spiegelmer technology is suitable to generate human medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Spiegelmers (German: Spiegel ϭ mirror) are structured biostable L-oligonucleotides that differ from their aptamer counterparts in their sugar moiety, which consists of mirrorimage L-(deoxy)ribose rather than D-(deoxy)ribose and makes Spiegelmers highly resistant to nucleases (11,12). Spiegelmers have already been described to act potently as inhibitors in vivo (13)(14)(15) and have proven to be exceptionally safe in two Phase I clinical studies. 4 Here, we report the generation of a Spiegelmer, binding to HMGA1 with high affinity.…”
Section: From Noxxon Pharma Ag Max-dohrn-strasse 8-10 D-10589 Berlimentioning
confidence: 99%